1999
DOI: 10.1063/1.478322
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic study of the C 1Σ+ state of 7LiH

Abstract: Forty-two vibrational (v=2–43) levels of the 7LiH C 1Σ+ excited electronic state have been observed by a pulsed optical–optical double resonance fluorescence depletion spectroscopic technique. The absolute vibrational numbering of the C 1Σ+ state is identified with the measurements of the isotopic shifts between 7LiH and 6LiH among several rotation-vibration bands of the C 1Σ+−A 1Σ+ electronic system, and it is further demonstrated by the consistency between observed spectral intensities and calculated ones. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 30 publications
1
28
0
1
Order By: Relevance
“…The OODR spectrum was detected by monitoring the fluorescence depletion of an X-A transition alternative to the PR pair of the pump laser, i.e., the monochromator detects the Figure 2 shows the fluorescence depletion spectra of the vibrational quantum levels near the dissociation limit of the C state. Successive rovibrational levels C (42, 2-10) were recorded via the intermediate levels A (8,(3)(4)(5)(6)(7)(8)(9)(10). There are some fluorescence-enhanced peaks, e.g., on the traces of the intermediate level A (8,9) or A (8,10).…”
Section: A Fluorescence Depletion Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…The OODR spectrum was detected by monitoring the fluorescence depletion of an X-A transition alternative to the PR pair of the pump laser, i.e., the monochromator detects the Figure 2 shows the fluorescence depletion spectra of the vibrational quantum levels near the dissociation limit of the C state. Successive rovibrational levels C (42, 2-10) were recorded via the intermediate levels A (8,(3)(4)(5)(6)(7)(8)(9)(10). There are some fluorescence-enhanced peaks, e.g., on the traces of the intermediate level A (8,9) or A (8,10).…”
Section: A Fluorescence Depletion Spectramentioning
confidence: 99%
“…Regarding the potential curve of the LiH C 1 Σ + state, which dissociates to Li(3s) + H(1s), a papillose inner potential well is formed due to the effect of the valence and Rydberg atomic configurations, and a major outer potential well is formed due to the interaction between the ionic and neutral electronic configurations. 3 The double-minimum potential commonly exists in the highly excited electronic states as can be seen in the example of LiH 4 and Na 2 . 5 The calculated permanent dipole moments of the NaH C 1 Σ + state exhibits an irregular variation at the avoided crossing regions (2.5, 6.5, and 12.5 Å), which is a well-known magnification of the contribution of covalent and ion-pair a) C.-C. Chu and H.-Y.…”
Section: Introductionmentioning
confidence: 99%
“…Among these studies, an optical-optical double resonance ͑OODR͒ experiment has shown that the C state, converging to the Li(3s)ϩH limit, presents a double-well potential shape due to a strong interaction with the Li ϩ uH Ϫ ionic state and local perturbations due to interactions with other neighboring electronic states. 2 These interactions have been theoretically studied by Gemperlé and Gadéa 4 in the frame of a non-BornOppenheimer approximation, involving eight electronic states of 1 ⌺ symmetry. For the highest vibrational levels of the C state, the interaction with the continuum of the A state is dominant and results in strong vibronic shifts, up to 10 cm Ϫ1 , and in nonradiative lifetimes rangs over six orders of magnitude, from nanoseconds to milliseconds.…”
Section: Introductionmentioning
confidence: 99%
“…In 1993, Stwalley and Zemke published a comprehensive review of experimental and theoretical work on the three lowest electronic states of LiH: X 1 Σ + , A 1 Σ + and B 1 Π [15]. More recent studies include extensive sub-Doppler laser spectroscopy of the A-X system [16], high precision studies of the ground-state by emission spectroscopy in the far and mid-infrared [12,17], and the first observation and characterization of the C 1 Σ + state [18,19]. All the experimental studies of gas-phase LiH have used hot sources.…”
Section: Introductionmentioning
confidence: 99%